Inventory and identification of species taro’s from genus Colocasia and Xanthosoma in Deli Serdang and Serdang Bedagai regency - etna adriana silaban; Emmy Harso Kardhinata; Diana Sofia Hanafiah (Universitas Sumatera Utara, 2019)
Inventory and identification of species taro’s from genus Colocasia and Xanthosoma in Deli Serdang and Serdang Bedagai regency. Supervised by Ir. Emmy Harso Kardhinata M.Sc., and Dr. Diana Sofia Hanafiah SP, MP., The purpose of the research is to inventory and identify of species taro’s from genus Colocasia and Xanthosoma in Deli Serdang and Serdang Bedagai regency. The research was conducted in Deli Serdang and Serdang Bedagai regency from May 2017 to August 2017. The research was dessigned by descriptive methode and the samples were collected based on accidental sampling technique. Morfological characteristic of taro were based on UPOV (International Union For The Protection Of New Varieties of Plant). The result showed that there were 11 genotip of taro. In the district Biru-biru, STM Hilir, and Dolok Masihul that included the highlands there were 5 genotip of taro are genotip 3, genotip 4, genotip 5, genotip 6, and genotip 7. In the district Patumbak that included the lowland there were 2 genotip of taro are genotip 1 and genotip 2. In the district Pantai Cermin and Perbaungan that included the beach there were 4 genotip of taro are genotip 8, genotip 9, genotip 10 and genotip 11. Some species of taro grow wild and have not been cultivated by peoples.